(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2025)
The WHO identifies non-pharmaceutical interventions (NPIs) as essential measures for COVID-19 control, characterized as behavioral phenomena. This study conducted a scoping review to examine analytical-behavioral contributions to NPI adherence. Using PRISMA-ScR, 51 articles published in 17 Behavioral Analysis journals in Portuguese, English, and Spanish were reviewed. The studies addressed ten NPIs, including home isolation and remote work (n=30), hand hygiene (n=9), risk communication for behavioral impact (n=9), and PPE use (n=8). Procedures like antecedent and consequent stimulus management, modeling, Behavioral Skills Training (BST), Habit Reversal Training (HRT), response cost, choice behavior, metacontingencies, macrocontingencies, and aversive control were extensively applied. The findings highlight Behavioral Analysis as a promising field for teaching and enhancing protective behavioral repertoires, providing effective tools to address public health emergencies.